2018
DOI: 10.4103/ejd.ejd_34_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on cytotoxicity of self-adhesive resin cements: Cell viability analysis

Abstract: Objective:The aim of the study was to assess, in vitro, the influence on cytotoxicity of heat treatment applied before photopolymerization, while mixing three self-adhesive resin cements, in an NIH/3T3 fibroblast cell culture, based on cell viability measures.Methods:Samples were divided into three groups: (1) no heat treatment while mixing (control), (2) 37°C, and (3) 60°C heat treatment while mixing. Cements were light-cured immediately after mixing and immersed in Dulbecco's Modified Eagle Media for the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
(48 reference statements)
2
18
0
Order By: Relevance
“…31 In agreement with our findings, other researchers also reported elevating cytotoxic effects with increasing exposure time to SARCs. [32][33][34] In a recent study, the cytotoxic effects of RU and BisCem (Bisco Inc.) SARCs on NIH/3T3 cells were examined, and it was detected that more cytotoxicity was encountered after 7 days of exposure than at the end of 24 h. 19 Besides, Pagano et al 35 reported that the cytotoxicity risk of a material was strongly related with the contact time, in agreement with the present study. Therefore, it may be suggested that resinbased restorative materials should be tested in both shortand long-term exposure periods.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…31 In agreement with our findings, other researchers also reported elevating cytotoxic effects with increasing exposure time to SARCs. [32][33][34] In a recent study, the cytotoxic effects of RU and BisCem (Bisco Inc.) SARCs on NIH/3T3 cells were examined, and it was detected that more cytotoxicity was encountered after 7 days of exposure than at the end of 24 h. 19 Besides, Pagano et al 35 reported that the cytotoxicity risk of a material was strongly related with the contact time, in agreement with the present study. Therefore, it may be suggested that resinbased restorative materials should be tested in both shortand long-term exposure periods.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, various cell types are used for cytotoxicity studies. In our study, we preferred the permanent NIH/3T3 cell line, like many other studies, 19,22 as recommended by ISO 7405, 26 which showed similar cytotoxicity response to pulp-derived cells. 30 Moreover, NIH/3T3 cells can be easily reproduced and used for a large scale testing.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…One disadvantage of the MTT assay is non-consistent estimation of number of viable cells in the resin content of tested materials [21] or the test itself [22] depending on the material tested, while several advantages of the test are obtaining rapid results, ease of application and visualization of cell density in small cell cultures [14,23,24]. In vitro studies that evaluated cytotoxicity of dental materials have commonly used fibroblast cells such as L929 and NIH/3T3 because of the reproducibility, availability and the resemblance of these cells to pulpal and gingival cells [1,6,[24][25][26][27]. Especially, NIH/3T3 which is one of the most commonly recommended cells for MTT assay, is a continuous cell line meaning that they can be reproduced fast and easy [26].…”
Section: Discussionmentioning
confidence: 99%
“…Resin components, for instance, are highly aggressive when in contact with cells: The literature reports a decrease in their aggressive behavior as soon as they are removed from the environment containing cells 14) . With the goal of improving polymer cross-linking and consequently increasing the rates of resinous polymer conversion, thus decreasing the number of residual monomers, some authors have proposed to increase photopolymerization time of resinous components 18,19) , whereas other authors have tested the use of external sources of heating before photopolymerization, within biologically acceptable limits [20][21][22][23][24][25] , resulting in immediate conversion gains, and also decreasing the concentration of final solvent in the adhesive system 26) . Temperatures of 23, 37, and 60ºC have been used to assess the mechanical properties of resinous compounds, and 60ºC has been reported to be the optimal temperature to improve polymer properties and system stability 20,22,26) .…”
Section: Introductionmentioning
confidence: 99%